Implications of an emerging EHR monoculture for hospitals and healthcare systems. (23rd October 2014) - Koppel, Ross; Lehmann, Christoph U
Abstract: In many hospitals and health systems, a 'new' electronic health record means a shift to one vendor: Epic, a vendor that dominates in large and medium hospital markets and continues its success with smaller institutions and ambulatory practices. Our paper examines the implications of this emerging monoculture: its advantages and disadvantages for physicians and hospitals and its role in innovation, professional autonomy, implementation difficulties, workflow, flexibility, cost, data standards, interoperability, and interactions with other information technology (IT) systems.